Prevalence of anxiety and depression and risk factors of their occurrence in medical students who had transferred COVID-19 - Yuryeva Людмила; Tymofeyev Роман; Shornikov Андрій; Kulbytska Марія (Psychosomatic Medicine and General Practice, 2021)
Background. The high prevalence of depressive and anxiety disorders in people with COVID-19 and the lack of data on depression and / or anxiety in higher education students who relapsed to COVID-19 led to the study. The purpose of the study was to assess the prevalence of anxiety and depression, as well as to identify risk factors for the development of these conditions in medical students of the DSMU. Methods. A one-off cross-sectional epidemiological study involving 154 respondents who voluntarily and anonymously completed a questionnaire with complaints, anamnestic data, and a self-assessment scale for depression PHQ-9 (cut-off point 10) and anxiety GAD-7 (cut-off point 10 points). Results. The prevalence of depression among medical students who relapsed to COVID-19 is 44.8%, which is higher than in the population of people who relapsed to COVID-19, the prevalence of anxiety is 27.9%, which is within the prevalence of other people who relapsed to COVID-19. COVID-19. The main independent factors in the development of depression were identified: anxiety (OR: 22,069; 95% [CI]: 7,941-61,335; p <0,05), hospitalization (OR: 5,443; 95% [CI]: 1,116-26,540; p < 0.05), CT / MRI (OR: 6,345; 95% [CI]: 1,728-23,296; p <0,05), glucocorticoids during illness (OR: 8,936; 95% [CI]: 2,495-31,999 p <0.05). The main factors of anxiety: fatigue (OR: 5,563; 95% [CI]: 1,605-19,286; p <0,05), weakness (OR: 9,477; 95% [CI]: 2,764-32,495; p <0,05) , hospitalization (OR: 11,568; 95% [CI]: 2,350-56,950; p <0,05), depression (OR: 22,069; 95% [CI]: 7,941-61,335; p <0,05). The level of blood saturation did not affect the development of depression and / or anxiety. Conclusions. Higher medical school students, unlike other COVID-19 survivors, have higher rates of depression. The identified risk factors for anxiety or depression indicate a large role for comorbid depression and anxiety, as well as the severity of COVID-19. Risk factors for anxiety and depressive disorders are probably not related to organic damage to the central nervous system, but to the psychological response to a potentially fatal disease.